Study on Modal Costs and Traffic Flows Report on Commodity and Passenger Flows Railways, Highways and Coastal Shipping Report IV Vol. I - Planning Commission (Planning Commission, 1980)
The Planning Commission, Government of India, vide their letter No.TSC/3(11)/77 dated 1.11.1977, entrusted Rail India Technical Economic Services Limited, New Delhi, to undertake 'Study of Comparative Costs and Commodity and Passenger Flows'. The Study was to be completed within a period of six months. Subsequently, in the inter-ministerial meeting held under the Chairmanship of the Secretary, Planning Commission, on 25.4.1978, the methodology developed for the study was discussed and the scope and duration for the study were revised. It was stipulated that the study would be completed by 31st of December, 1979.
Transport Policy Planning Project Planning Commission Government of India
Transport Policy Planning Project Planning Commission Government of India